1992
DOI: 10.1084/jem.176.4.963
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of HLA class I alleles in natural killer (NK) cell-specific functions: expression of HLA-Cw3 confers selective protection from lysis by alloreactive NK clones displaying a defined specificity (specificity 2).

Abstract: This study was designed to identify the target molecules of the natural killer (NK) cell-mediated recognition of normal allogeneic target cells. As previously shown, the gene(s) governing the first NK-defined allospecificity (specificity 1) were found to be localized in the major histocompatibility complex region between BF gene and HLA-A. In addition, the analysis of a previously described family revealed that a donor (donor 81) was heterozygous for three distinct NK-defined allospecificities (specificities 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
133
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(140 citation statements)
references
References 29 publications
5
133
2
Order By: Relevance
“…These exPBNK can mediate cytotoxicity of allogeneic and autologous cancer cell lines by specifically activating receptor-ligand interactions. Another mechanism of tumor-cell resistance is by upregulating the expression of KIR-inhibitory ligands (46). In our study, we found that the expanded NK cells express KIRs, such as KIR2DL1, KIR2DL2/3, and KIR3DL1, and Raji, Raji-2R, and Raji-4RH cells express high-level HLA-ABC ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 61%
“…These exPBNK can mediate cytotoxicity of allogeneic and autologous cancer cell lines by specifically activating receptor-ligand interactions. Another mechanism of tumor-cell resistance is by upregulating the expression of KIR-inhibitory ligands (46). In our study, we found that the expanded NK cells express KIRs, such as KIR2DL1, KIR2DL2/3, and KIR3DL1, and Raji, Raji-2R, and Raji-4RH cells express high-level HLA-ABC ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Lysis occurs when the combination of activation signals overcomes any inhibitory signals provided by ligands on the target cell. The principal ligands for inhibitory molecules appear to be the HLA class I Ags, and susceptibility of tumors to NK-mediated lysis was shown to be related to the degree of expression of these molecules (14). In contrast, the nonsusceptibility of the B lymphoma cell line RAJI to NK-mediated lysis has been attributed to its expression of all of the known classes of ligands for NK-inhibitory molecules.…”
Section: Discussionmentioning
confidence: 95%
“…In primary leukemias, lack of inhibition was not sufficient to confer cytotoxicity [20], but cell lines were rendered NK-resistant by HLA-C transfection, thus indicating a requirement of MHC class I down-regulation for NK-cell activity [21]. On the other hand, cells displaying normal levels of MHC class I were susceptible to NK-cell lysis if effector cells became otherwise activated [22,23].…”
Section: Introductionmentioning
confidence: 99%